O03.3 Sex industry regulation, sex worker health and sti/hiv prevention. (8th July 2017) - Powell, Victoria; Karlsen, Eva
Abstract : Introduction: The ability of sex workers to access healthcare and STI/HIV prevention education and tools is directly impacted by policy and law. Australia provides a unique case study of the direct effects of criminalisation, licensing, and decriminalisation on access to healthcare and rates of STI/HIV transmission as each state and territory has differing models of regulation operating side by side. New South Wales decriminalised sex work in 1995 in response to government findings of systemic police corruption; criminal laws repealed and police no longer regulators, sex work is regulated through standard occupational, planning and industrial mechanisms. Methods: Scarlet Alliance, the peak national sex work organisation, collects data directly from sex workers via forums, working groups and surveys. We conducted an in-depth, five stage consultation with sex workers from a range of genders, experiences and backgrounds. We reviewed health research and government reports to examine policy successes and areas in need of reform. Results: Under decriminalisation NSW sex workers have better access to healthcare and STI/HIV education and prevention tools including free, confidential and anonymous sexual health services as well as peer-led services. Higher rates of safer sex, lower rates of STIs and improved Workplace Health and Safety were also evident, while in other jurisdictions sex workers continue to face barriers to treatment and other health services and often work outside legal frameworks. Conclusion: Decriminalisation is the optimal regulatory model and is supported by the UNFPA, UNDP, UNAIDS, WHO and Amnesty International as critical to HIV prevention and for human rights. Despite 22 years of evidence of its success, barriers remain to the uptake of this model in Australia and globally including political pressure to criminalise clients, hostile funding environments, the booming "rescue industry and institutional discrimination. The Australian case study supplies valuable evidence for governments, researchers, the health sector and the global sex work community.